2016
DOI: 10.4236/ojl.2016.52005
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and the Limitations of Language

Abstract: The elusiveness of our words, their inability to fully capture reality, and our natural tendency to hear only what fits with our existing framing lenses contribute to the limitations of language. These inadequacies are especially important when it comes to leadership since language is the leader's most important resource. In order to be effective, leaders must be aware that language creates contexts and that contexts are, by nature, limiting. This awareness doesn't immunize them from the limitations of languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Research has consistently demonstrated that language is not merely a tool for communication but also shapes perceptions, relationships, and organizational dynamics. Souba and Souba (2016) and Charteris- Black (2006) argue that language is a primary medium through which leadership is exercised, and leaders who can effectively communicate their vision and strategy in a language that resonates with diverse stakeholders are more likely to inspire commitment and achieve organizational goals.…”
Section: Language In Businessmentioning
confidence: 99%
“…Research has consistently demonstrated that language is not merely a tool for communication but also shapes perceptions, relationships, and organizational dynamics. Souba and Souba (2016) and Charteris- Black (2006) argue that language is a primary medium through which leadership is exercised, and leaders who can effectively communicate their vision and strategy in a language that resonates with diverse stakeholders are more likely to inspire commitment and achieve organizational goals.…”
Section: Language In Businessmentioning
confidence: 99%
“…This implicit leadership theory-leadership equated with a person in charge who stands out-is pervasive (Souba and Souba, 2016). We learned to think this way from our superiors and role models.…”
Section: The Need For Definitions and Shared Understandingsmentioning
confidence: 99%
“…People use spoken and written expressions to convey ideas and create requests; in leadership, language acts as their most valuable resource (Marquet, 2020;Souba & Souba, 2016;Ting, 2010). It can be strenuous to set courses, create guidelines, or develop standards without proper use of language.…”
Section: Making Sense Of the Dynamics Of Language Style And Leadershipmentioning
confidence: 99%